Tanggung Jawab Ahli Waris dalam Pengembalian Aset Negara Hasil Tindak Pidana Korupsi oleh Terpidana yang Meninggal Dunia - Putu Aditya Witanaya Putra; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
Corruption is a very serious problem because it is detrimental to State finances. Therefore, several actions are needed to recover state financial losses by paying compensation for state assets. This study aims to determine the responsibility of the heirs in returning state assets from corruption committed by their deceased parents and to analyze the payment mechanism for the return of state assets resulting from corruption. This study uses normative research with a statutory approach. The results of the analysis show that the responsibility of the heirs in returning state assets depends on the evidence of court decisions and the mechanism regarding replacement money in returning state assets in accordance with the amount of assets convicted of corruption. Then, the replacement money mechanism for returning state assets from the proceeds of corruption in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Corruption Eradication explains that corruption convicts are required to pay the amount of replacement money according to the results corrupted by the convict. The conclusion is that state financial losses caused by corruption convicts who have passed away are transferred to their heirs according to evidence in court decisions.